An Assessment of Food Safety Knowledge and Practices in the Ghanaian Hospitality Industry - Stephen T. Odonkor; Carolyn J. A. Odonkor (Journal of Food Quality)
Food safety is critical for public health and economic development. The hospitality industry offers a variety of food services, led by food handlers with diverse background. The aim of this paper is to evaluate food safety knowledge and practices among food handlers in the Ghanaian hospitality sectors, with the purpose of informing public policy and improving food safety. A cross-sectional survey study was conducted between February and May 2019. Data were obtained from food handlers working in the Ghanaian hospitality industry (N = 306). The findings of the study indicate that most (52.9%) respondents who work in restaurants had knowledge about food safety principles. Lack of training and education was identified by 63.1% of the respondents as a major barrier to food safety. Interestingly, 75.8% of the respondents indicated that food safety practice is not the responsibility of the kitchen staff only. Diarrhea (35.95%), cholera (35.62%), and typhoid (27.42%) were identified as major diseases associated with improper handling of food. Only 65.69% of the respondents undergo annual medical screening at their workplaces. There is correlation between food safety practice and variables such as marital status, type of residence, age, and education level. Educational campaigns coupled with strict law enforcement should be put in place to ensure that food safety rules and guideline are effectively implemented in the hospitality food industry. Training programs should be organized for food vendors and other stakeholders in the food industry as well. Finally, there should be proactive supervision by local government officials to ensure that good sanitation and hygienic conditions are maintained within the food sectors.